Determination of ?iroctone Olamine (Octopirox) in Bulk by UV Spectrophotometric Method - Antypenko, Lyudmyla M; Solodovnyk, Vitaliy A (Dhaka University Journal of Pharmaceutical Sciences, 2017)
A simple and low-cost UV-spectrophotometric method has been developed and validated for the quantification of Octopirox in bulk. The linearity was found at 307 ± 1 nm in 10-50 ?g/ml solution of ethanol-water (1:3, v:v) with r2 = 0.99. The limit of detection was found to be 1.18 µg/ml, while the limit of quantification was 3.58 µg/ml. The method was validated for linearity, accuracy, precision, range, ruggedness and robustness. Dhaka Univ. J. Pharm. Sci. 16(1): 37-42, 2017 (June)